2019
DOI: 10.2147/ott.s198014
|View full text |Cite
|
Sign up to set email alerts
|

<p>Expression and significance of LncRNA MNX1-AS1 in non-small cell lung cancer</p>

Abstract: Objective: To investigate the expression of LncRNA MNX1-AS1 in NSCLC and its effect on NSCLC cell lines. Methods: In this experiment, the expression of LncRNA MNX1-AS1 was detected by qRT-PCR in 116 NSCLC samples, and the correlation between MNX1-AS1 and NSCLC patients was further analyzed by chi-square test. The prognostic value of MNX1-AS1 was assessed by Kaplan-Meier survival curve. The expression of MNX1-AS1 in NSCLC cell line A549 was knocked down, and the effects of MNX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
(17 reference statements)
0
16
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs), a heterogeneous class of transcripts with a minimum length of 200 bases and limited protein-coding potential, was recently presented as a potential target for numerous cancers by interacting with RNAs and proteins (3). LncRNA MNX-AS1, known as Motor neuron and pancreas homeobox 1-antisense RNA1, was reported overexpressing in several tumor types such as gastric cancer, non-small cell lung cancer (NSCLC) and breast cancer and others (4)(5)(6). However, how MNX-AS1 leads to the progression and poor survival outcome of breast cancer, especially of TNBC needed to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs), a heterogeneous class of transcripts with a minimum length of 200 bases and limited protein-coding potential, was recently presented as a potential target for numerous cancers by interacting with RNAs and proteins (3). LncRNA MNX-AS1, known as Motor neuron and pancreas homeobox 1-antisense RNA1, was reported overexpressing in several tumor types such as gastric cancer, non-small cell lung cancer (NSCLC) and breast cancer and others (4)(5)(6). However, how MNX-AS1 leads to the progression and poor survival outcome of breast cancer, especially of TNBC needed to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 882 patients from the all eligible articles were included to evaluate prognostic value of MNX1-AS1 (presented in Table 1). All articles covered gastric cancer(GC) (n = 3) [8][9][10], lung cancer (LC) (n = 3) [6,20,21], other cancer(n = 3) including: esophageal squamous cell carcinoma (ESCC), cervical cancer (CC), epithelial ovarian cancer (EOC) [14,18,22].…”
Section: Search Results Of Eligible Studiesmentioning
confidence: 99%
“…Discussion MNX1-AS1, also known as MAYA and CCAT5, is located at chromosome 7q36.3 [6]. Upregulation of MNX1-AS1 expression has been found in a variety of cancers, including gastric cancer [8][9][10], lung cancer [6,20,21], esophageal squamous cell carcinoma [14,15], and estrogen-dependent cancer [7,18,22], etc. MNX1-AS1 play a role of functional oncogene in addition to activating AKT/mTOR pathway and its natural sense transcript MNX1 in breast cancer cells, it also promotes the process of EMT [7].…”
Section: Involvement Of Mnx1-as1 In Carcinogenesismentioning
confidence: 99%
“…One important lncRNA, MNX1-AS1, was upregulated and involved in tumorigenesis of diverse malignant tumors, including non-small cell lung cancer (NSCLC) 35 , lung adenocarcinoma 36 , and Esophageal squamous cell carcinoma (ESCC) 37 . It was revealed that MNX1-AS1 was related to TNM stage and lymph node metastasis in NSCLC, and associated with a poor prognosis of NSCLC patients 35 . MNX1-AS1 expression was demonstrated to correlate with the poor prognosis of lung adenocarcinoma patients 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the abnormal expression of some lncRNAs in ICC samples is a well-confirmed phenomenon, the functional mechanisms of lncRNAs remain to be elucidated. One important lncRNA, MNX1-AS1, was upregulated and involved in tumorigenesis of diverse malignant tumors, including non-small cell lung cancer (NSCLC) 35 , lung adenocarcinoma 36 , and Esophageal squamous cell carcinoma (ESCC) 37 . It was revealed that MNX1-AS1 was related to TNM stage and lymph node metastasis in NSCLC, and associated with a poor prognosis of NSCLC patients 35 .…”
Section: Discussionmentioning
confidence: 99%